Health risk assessment of exposure to Polycyclic Aromatic Hydrocarbons in bread from Iranian markets: Application of monte carlo simulation approach - Najmeh Khodadadi; Masoumeh Saghi; Sina Mashayekhi; Negin Bashirian; Fateme Asadi Touranlou; Seyedeh Belin Tavakoly Sany (PLoS ONE, 2026)
Background Polycyclic aromatic hydrocarbons (PAHs) are persistent environmental contaminants formed during high-temperature processing of food and are associated with both carcinogenic and non-carcinogenic health effects. Methods A total of 96 bread samples (Lavash, Sangak, and Barbari) were collected from industrial and traditional bakeries across eight municipal zones of Mashhad, Iran. Sixteen priority PAHs were quantified by GC-MS after microwave-assisted saponification and DLLME clean-up. Toxic equivalent concentrations (BaPeq), daily dietary exposure, incremental lifetime cancer risk (ILCR), and Monte Carlo probabilistic modelling (100,000 iterations) were used for risk characterisation. Results Mean Σ₁₆PAHs were significantly higher in traditional breads (68.63 ± 4.57 µg/kg) than industrial breads (39.87 ± 3.68 µg/kg; p < 0.001), with Lavash showing the highest levels (66.58 ± 6.02 µg/kg) and Sangak the lowest (40.95 ± 1.63 µg/kg). Naphthalene dominated light PAHs; fluoranthene and pyrene were predominant heavy PAHs. Mean BaP concentrations (0.05–0.10 µg/kg) were below the EU limit of 1 µg/kg. Mean TEQ was 0.18 µg/kg, with BaP contributing ~58%. Probabilistic assessment showed acceptable to low carcinogenic risk, slightly higher for traditional baking. Sensitivity analysis identified BaP as the primary driver. Compared globally, PAH levels in these Iranian breads indicate an acceptable risk, though continued monitoring and regulation are needed. Conclusion Current PAH exposure via bread in Mashhad is generally acceptable, but traditional baking markedly increases contamination. Transition to indirect-heating ovens, improved ventilation, and regular monitoring are recommended to minimise exposure.